PENERAPAN MODEL PEMBELAJARAN PROBLEM-BASED LEARNING BERBANTUAN VIDEO TUTORIAL UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS XIIB AKL SMK NEGERI 1 SINGARAJA PADA SEMESTER GANJIL TAHUN PELAJARAN 2022/2023 - Noer Endah Pramudji Setyaningrum (Universitas Panji Sakti, 2022)
AbstractThe purpose of implementing this classroom action research was to increase the learning activity of class XIIB AKL students of SMK Negeri 1 Singaraja in the odd semester of the academic year 2022/2023 in taking the Practical Accounting subjects for Companies, Services, Trade and Manufacturing. This research was conducted on 34 students as research subjects. The way this was done was through the application of a problem-based learning (PBL) learning model assisted by video tutorials. The research was conducted in two cycles, each cycle carried out with the stages of planning, implementing, observing and reflecting. To collect research data, student learning activity questionnaire was used and to analyze the data, descriptive analysis was used. Judging from the evaluation results that have been carried out there was an increase in student learning activity from the initial data with an active percentage of 38.23% (low category), to 55.88% (medium category) in cycle I and to 85.29% (high category) in cycle II. Through the results of the analysis obtained, it can be concluded that the application of PBL assisted by video tutorials can increase students’ active learning.Keywords:Problem-based learning models, video tutorials, active learning